The construction of a collective action for the generation of housing projects. Case study of a social group in an average city in Argentina - Girado, Agustina (Revista Chilena de Antropología, 2020)
The paper recovers the experience of struggle and work of a social group dedicated to the generation of housing projects in an average city in the province of Buenos Aires (Argentina). From this, it reflects on the processes of social interaction in various spaces -family, neighbourhood and organizational- as well as the characteristics -structural and symbolic- of the city that enabled the generation of a collective action that proved strategic to guarantee access to urban land and housing for vast social sectors. In addition to this, it seeks to account for the disputed, unfinished, fluid and often truncated character, of the processes, actions and experiences displayed by the group in relation to the realization of certain objectives and their registration in more global historical and political processes. What was developed in the article follows a doctoral research in Social Anthropology that adopted an ethnographic approach to understand social processes.